Potential marker of endothelial dysfunction in patients with various grade of cardiovascular risk - A. Yu. Gorshkov; N. G. Gumanova; S. A. Boytsov (Кардиоваскулярная терапия и профилактика)
Aim. As the endothelial glycocalix (EG) — gel-like layer on the surface of endothelium, participates in normal endothelial functioning maintenance, search for markers that characterize its condition, is of high scientific interest. Aim of the study — to evaluate clinical and diagnostic opportunities for novel EG marker, related to thickness and plasticity of EG, represented as perfused boundary region (PBR, μm) of erythrocytes.Material and methods. Totally, 208 patients included (123 men, 85 women) at the age 40-65 y.o., with various level of cardiovascular risk by SCORE, and coronary heart disease (CHD). EG of microvessels was charterized via PBR, that was measured with dark field capillaroscope with diod light of green spectrum.Results. With the values of PBR >2 μm there is worsening of morphofunctional state of arteries of different localizations, and microcirculatory vessels, level of apolipoprotein A1 decreases, as structure protein of high density lipoproteins, and prevalence of carotid atherosclerosis increases two times, of CHD — 2,5 times (p<0,05). Tendency is marked to the increase of prevalence of higher cardiovascular risk by SCORE. Statins intake in CHD patients is related to PBR decrease: 1,86±0,20 μm vs 2,05±0,22 μm (p<0,05).Conclusion. Novel marker of EG, PBR, in values >2 μm, is associated with worsening of microcirculatory vessel condition, and of large arteries, prevalence of stenosing atherosclerosis of carotid arteries and CHD, that points on its properties of surrogate marker of endothelial dysfunction and further opportunities for its implementation with diagnostical aims.